2014
DOI: 10.13102/sociobiology.v59i1.677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coptotermes formosanus and Coptotermes gestroi (Blattodea: Rhinotermitidae) Field Sites and Seasonal Foraging Activity in Hawaii

Abstract: Field surveys were carried out from January 2010 to June 2011 to record the environmental properties of Coptotermes formosanus Shiraki and C. gestroi (Wasmann) (Blattodea: Rhinotermitidae) field sites on the island of Oahu, Hawaii; and to document seasonal patterns in C. formosanus and C. gestroi foraging activity. The two field sites selected differed in elevation, soil characteristics, vegetation, and mean temperature and humidity patterns. The C. formosanus colony was located on the Manoa campus of the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…It was believed that the variations of temiite activity are closely related to temperature fluctuations (Sen-Sarma and Mishra 1969, Evans and Gleeson 2001, Hapukotuwa and Grace 2012a. Foraging activity is a direct measurement of damage potential by subterranean termites.…”
Section: Resultsmentioning
confidence: 99%
“…It was believed that the variations of temiite activity are closely related to temperature fluctuations (Sen-Sarma and Mishra 1969, Evans and Gleeson 2001, Hapukotuwa and Grace 2012a. Foraging activity is a direct measurement of damage potential by subterranean termites.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, stake survey and IG stations have been successfully used, at least partially, to detect and monitor C. gestroi populations by previous studies, in Thailand (Sornnuwat et al 1996), Little Cayman (Su et al 2000), Brazil (Santos et al 2010), Hawaii (Hapukotuwa and Grace 2012a), and Malaysia (Majid and Ahmad 2015). While our results appear at first to contradict with C. gestroi studies in other regions, a closer look indicated that this termite species is not easily detected by soil survey methods in certain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about eight introduced termite species at Hawaii is given by Grace et al . () and Hapukotuwa and Grace (), and drywood termite Cryptotermes brevis Walker at six islands (from nine) of Azores archipelago by Guerreiro et al . ().…”
Section: Invasions Of Termitesmentioning
confidence: 99%
“…Detailed information about eight introduced termite species at Hawaii is given by Grace et al (2002) and Hapukotuwa and Grace (2012), and drywood termite Cryptotermes brevis Walker at six islands (from nine) of Azores archipelago by Guerreiro et al (2014). Attempts to eradicate the invading termites are usually futile; only two known cases of successful eradication are known: Coptotermes formosanus from South Africa and C. frenchi from New Zealand (Chouvenc et al 2015).…”
Section: Invasions Of Termitesmentioning
confidence: 99%